2009 IEEE International Conference on Cluster Computing and Workshops 2009
DOI: 10.1109/clustr.2009.5289155
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating SIFT on parallel architectures

Abstract: SIFT is a widely-used algorithm that extracts features from images; using it to extract information from hundreds of terabytes of aerial and satellite photographs requires parallelization in order to be feasible. We explore accelerating an existing serial SIFT implementation with OpenMP parallelization and GPU execution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…As evaluated in [24], their design actually gained a speedup of 6.0X from its parallelism for 16-core machine. Moreover, Seth et al [20] explored and evaluated parallel SIFT using large images as input in both multi-core CPU and GPGPU. They found that SIFT requires huge memory space when the input image size is large.…”
Section: B Previous Acceleration Effortsmentioning
confidence: 99%
See 1 more Smart Citation
“…As evaluated in [24], their design actually gained a speedup of 6.0X from its parallelism for 16-core machine. Moreover, Seth et al [20] explored and evaluated parallel SIFT using large images as input in both multi-core CPU and GPGPU. They found that SIFT requires huge memory space when the input image size is large.…”
Section: B Previous Acceleration Effortsmentioning
confidence: 99%
“…However, no satisfied results are achieved in these works. For example, the researches in [15] [20] only achieve about a speedup of 6X on a 16-core machine. It is obvious that a large gap exists between their results and the ideal speedup, which means that there are some limitations in their parallel implementations or in original serial IFEAs.…”
Section: Introductionmentioning
confidence: 97%
“…And this approach has been further developed in [10], which utilizes both CPU and GPU by combining OpenMP, SSE (Streaming SIMD Extension) and CUDA (Compute Unified Device Architecture) programming. Then, [11] applied GPU and OpenMP based SIFT implementation to massive satellite image processing. One of the disadvantages of this approach is that special hardware is required, which increased the cost.…”
Section: Related Workmentioning
confidence: 99%
“…GPUs have been shown to provide great speedup on a wide range of computer vision algorithms, including SIFT [7,8,9,10]. However, this success has mostly been confined to desktop GPU applications.…”
Section: Prior Workmentioning
confidence: 99%